PROSPECTS OF USING SUGGESTIVE TECHNOLOGY IN DISTANCE EDUCATION - Puliak , Olha; Myronenko , Natalya (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
An article on the possibilities and prospects of using suggestive learning technology in the conditions of distance learning. Taking into account the circumstances that force male and female students in Ukraine to carry out educational activities mainly in the distance form of education, there is a loss of interest and motivation to study, and as a result, a loss of the quality of education. Therefore, teachers find and use such learning technologies that can activate the creative and intellectual sphere of activity of students and increase positive motivation for educational activities. As such technology, the authors proposed a suggestive technology, which differs from others in that its introduction into the educational learning process is carried out on the basis of emotional suggestion, which leads to over-memorization. The authors concluded that the introduction of suggestive learning into the educational process activates the creative and intellectual sphere of students, improves work efficiency and reduces fatigue, creates a positive emotional microclimate and makes the educational process more productive.